Analisis Penerapan Suply Chain Management Pada Pengadaan Material Proyek Normalisasi Saluran Drainase Pasar Wadung Asri Sidoarjo - Yuda Ardiansyah; Dira Ernawati (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
As Time And Human Civilization Progress, The Construction Industry Is Also Developing Rapidly, Starting From Advances In Technology Used To Increasing Competitors, Both Foreign Competitors And Local Competitors. The Application Of Supply Chain In The Construction Industry Is Believed To Be One Of The Strategic Efforts To Increase The Competitiveness And Performance Of A Construction Company. In This Research, An Analysis Of The Application Of Supply Chain Management (SCM) Will Be Carried Out In The Wadung Asri Market Drainage Channel Normalization Project. This Research Aims To Find Out Whether Contractors Have Implemented The Supply Chain Management (SCM) Concept In Their Material Procurement Process. The Research Results Show That In The Project Material Procurement Process, The Contractor Has Not Implemented The Supply Chain Management (SCM) Concept Significantly. This Can Be Seen From Decisions In Selecting Suppliers Which Are Only Based On The History Of Cooperation Without Considering Other Factors. Apart From That, There Were Delays In The Arrival Of Materials Which Resulted In Project Work Being Delayed From The Initial Plan. Therefore, It Is Necessary To Improve The Goods Procurement System That Has Been Running So Far By Implementing The Supply Chain Management Concept.